2022
DOI: 10.3390/life12020282
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Insight into Cold Stress Response in Two Contrasting Maize Lines

Abstract: Maize (Zea mays L.) is sensitive to a minor decrease in temperature at early growth stages, resulting in deteriorated growth at later stages. Although there are significant variations in maize germplasm in response to cold stress, the metabolic responses as stress tolerance mechanisms are largely unknown. Therefore, this study aimed at providing insight into the metabolic responses under cold stress at the early growth stages of maize. Two inbred lines, tolerant (B144) and susceptible (Q319), were subjected to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 97 publications
(117 reference statements)
2
4
0
Order By: Relevance
“…Notably, the levels of two alkaloids, p-coumaroyl putrescine and p-coumaroyl cadaverine, were significantly increased by 95 and 59 fold, respectively. Yu et al [ 72 ] found that p-coumaroyl glucoside is one of the primary differential accumulative metabolites of maize frost tolerance. Therefore, we believe that the accumulation of p-coumaroyl may be a metabolite formed during plant resistance to low-temperature stress.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the levels of two alkaloids, p-coumaroyl putrescine and p-coumaroyl cadaverine, were significantly increased by 95 and 59 fold, respectively. Yu et al [ 72 ] found that p-coumaroyl glucoside is one of the primary differential accumulative metabolites of maize frost tolerance. Therefore, we believe that the accumulation of p-coumaroyl may be a metabolite formed during plant resistance to low-temperature stress.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance, a chilling tolerant inbred line of maize had an increased phenolic content (i.e. phenolic acids and flavonoids) when subjected to cold stress (Yu et al, 2022). Similarly, we found that the content of rosmarinic acid increased in response to low temperature cultivation (Chapter 4).…”
Section: Can Lowered Temperature Improve Chilling Tolerance?supporting
confidence: 79%
“…Furthermore, sinapyl alcohol is significantly upregulated in the tolerant Zea mays cultivar B144 (Yu et al, 2022). In addition, succinate accumulates when plants are exposed to cold stress (Song et al, 2016;Xie et al, 2022).…”
Section: Phenylpropanoid Biosynthesis Involved In Cold Resistancementioning
confidence: 99%